Effect of structural viscosity on the propagation of ultrasonic waves in dilute suspensions - Kowalski, S. J.; Sikorski, M. (Archives of Acoustics, 2003)
The aim of the paper is a rigorous derivation of the formulas determining the phase velocity and the attenuation coefficient of ultrasonic waves propagating in diluted suspensions, and experimental verification of these theoretical predictions. In experiments, the ultrasonic waves were propagating trough the suspension composed of peat suspended in water. The satisfactory fitness of the values implied by the theoretically obtained formulas and the respective expeimental data allow us to recommend the ultrasonic method as a non-invasive, rapid, accurate and cheap method that might be used for assessments of the solid content in suspensions.